INTENSITAS ANCAMAN KEAMANAN SISTEM INFORMASI AKUNTANSI KOMPUTERISASIAN - YULIUS KURNIA SUSANTO; RATIH HANDAYANI (Jurnal Bisnis dan Akuntansi, 2008)
The objective of the paper was (1) there are significant security threats of CAIS on the organization types, (2) there is difference among the organization types regarding the security threats of CAIS, (3) there are difference between integration-on line and integration-manual CAIS regarding the security threats of CAIS. Eighty four respondents from Jakarta organizations had participated in this research. The collecting data used a questionnaire survey via electronicmail and post. Data were analyzed using a Kruskal-Wallis test. The resultsshowed that first there is significant security threats of CAIS in Jakarta Organizations, like that the accidental entry of bad data, accidental destruction of data, employees’ sharing of passwords and introduction of computer viruses the to CAIS are the significant security threats of CAIS in Jakarta Organizations. Second, there is no difference among the organization types regarding the security threats of CAIS. Third, there is no difference between integration-on line and integration-manual CAIS regarding the security threats of CAIS. But, there is difference between integration-on line and integration-manual CAIS regarding introduction of computer viruses to the CAIS.